A short overview on vocational education and training in Ukraine : current status, challenges and reform intentions - Leu-Severynenko, Snizhana [Verfasser] (My University, 2022)
"The following article deals with the current state of vocational education and training as well as with planned reform projects and those already being implemented. In the first step, the challenges, obstacles and progress up to the outbreak of the war are presented. In a further step, the text looks at the plans for the post-war period. Aspects of legislation, financial support, and coordination needs are addressed. The contributions of international donor organisations are also presented and classified in this context. The author analyses the plans for reconstruction and further development of vocational education and training presented by the Ukrainian government at international and national levels. As a result, she suggests possible directions for the development of vocational education and training that are in line with the current reform process in Ukraine." (BIBB-Autorenreferat)

„Der folgende Beitrag befasst sich mit dem aktuellen Stand der Berufsbildung sowie mit geplanten und bereits umgesetzten Reformvorhaben. In einem ersten Schritt werden die Herausforderungen, Hindernisse und Fortschritte bis zum Ausbruch des Krieges dargestellt. In einem weiteren Schritt befasst sich der Text mit den Plänen für die Nachkriegszeit. Dabei werden Aspekte der Gesetzgebung, der finanziellen Unterstützung und des Koordinierungsbedarfs angesprochen. Auch die Beiträge der internationalen Geberorganisationen werden in diesem Zusammenhang dargestellt und eingeordnet. Die Autorin analysiert die von der ukrainischen Regierung auf internationaler und nationaler Ebene vorgelegten Pläne für den Wiederaufbau und die weitere Entwicklung der Berufsbildung. Als Ergebnis schlägt sie mögliche Richtungen für die Entwicklung der Berufsbildung vor, die mit dem aktuellen Reformprozess in der Ukraine in Einklang stehen.“ (Autorenreferat; BIBB-Doku)
Keywords: I 2.2.2 Osteuropa; S 1 Stufen der Berufsbildung; S 2.3 Berufsbildungspolitik; 370; Berufsbildung; Berufsbildungssystem; Bildungssystem; Internationale Zusammenarbeit; Ukraine